2019
DOI: 10.1159/000498977
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Characteristics of Atypical Glandular Cells Determined by Cervical Cytology in Japan: Survey of Gynecologic Oncology Data from the Obstetrical Gynecological Society of Kinki District, Japan

Abstract: Background: The purpose of this study was to clarify the clinicopathological characteristics of, and the clinical approach used to identify, atypical glandular cells (AGCs) in Japan based on cervical cytology screening. Objectives: This study included 1,254 patients with AGCs who underwent cervical cytology. Method: Data from patients with AGCs were used to examine the practical management of AGCs and the histological results. Results: The incidence of AGCs was 0.20% (1,254/614,791). The 1,254 AGC cases includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 37 publications
4
12
0
Order By: Relevance
“…Suresh et al reported a 66.7% malignancy rate, while Selvaggi and Kirwan reported malignancy rates of 78% and 81.6%, respectively, but similar with other studies, our study showed that endometrial cancer was the most common cancer 21‐23 . The most common primary sites for metastatic tumours in AGC cases have been reported to be the colon and breast in the literature 8,12,13,20 …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Suresh et al reported a 66.7% malignancy rate, while Selvaggi and Kirwan reported malignancy rates of 78% and 81.6%, respectively, but similar with other studies, our study showed that endometrial cancer was the most common cancer 21‐23 . The most common primary sites for metastatic tumours in AGC cases have been reported to be the colon and breast in the literature 8,12,13,20 …”
Section: Discussionsupporting
confidence: 89%
“…The largest sample of AGC in the literature was the study of Toyoda et al In their study, published in 2019 and including 1254 AGC cases, they found 182 (14.5%) premalignant lesions and 364 (29.1%) invasive carcinomas. Among the invasive carcinomas, endometrial carcinomas were found at a rate of 57.4%, followed by cervical adenocarcinoma (29.1%), ovarian carcinoma (7.1%), and squamous cell carcinoma (5.2%), and 4 cases had metastasis (1.1%) 20 . Some studies also reported higher malignancy rates than expected in AGC cases.…”
Section: Discussionmentioning
confidence: 91%
“…If investigations are normal, the current policy of returning these women to routine recall or offering cytological follow‐up in 12 months, rather than 6, appears risky in view of the high rates of significant lesions in women with glandular cytology, HR HPV and negative colposcopy . As reported in this paper, the accuracy of colposcopy is moderate and it is possible that the punch biopsy may not be representative of the area of pathology.…”
Section: Discussionmentioning
confidence: 86%
“…Our finding of 1.4% is more than 0.2% AGC found in a large study done in Japan and reported in 2019. 18 The incidence of AGC in a 10 year analysis of conventional Pap smears in Luxembourg was 0.05%. 19 Out of 39,484 Pap smears, the percentage of AGUS cells was 1.2% in a study published in 1998, which is fairly similar to our study.…”
Section: Discussionmentioning
confidence: 97%